How to Integrate Experimental Research Approaches in Ecological and Environmental Studies: AnaEE France as an Example - Clobert, Jean; Chanzy, André; Le Galliard, Jean-François; Chabbi, Abad; Greiveldinger, Lucile; Caquet, Thierry; Loreau, Michel; Mougin, Christian; Pichot, Christian; Roy, Jacques; Saint-André, Laurent (Frontiers in Ecology and Evolution, 2018)
Human activities have altered continental ecosystems worldwide and generated a major environmental crisis, prompting urgent societal questions on how to best produce goods while at the same time securing sustainable ecological services and raising needs to better understand and predict biodiversity and ecosystems dynamics under global changes. To tackle these questions, experimentation on ecosystems is necessary to improve our knowledge of processes and to propose scientifically sound management strategies. Experimental platforms able to manipulate key factors of global change and including state of the art observation methodologies are available worldwide but how to best integrate them has been rarely addressed. Here, we present and discuss the case of the national research infrastructure AnaEE France dedicated to the study of continental ecosystems and designed to congregate complementary experimental approaches in order to facilitate their access and use through a range of distributed and shared services. The conceptual design of AnaEE France includes five modules. Three modules gather experimental facilities along a gradient of experimental control ranging from highly controlled Ecotron facilities, semi-natural field mesocosms to in natura experimental sites covering major continental ecosystems (forests, croplands, grasslands and lakes). In addition, AnaEE France also includes shared instruments that can be implemented in experiments and analytical platforms specifically dedicated to environmental biology. To promote reuse of data, generalize results and improve predictive models, AnaEE France further gathers modelling and information systems. The implementation of AnaEE France allowed for mutual synergies, improved the technical skills, stimulated new experiments and helped our scientific community to enter into the big data sharing era.